2015
DOI: 10.1159/000441142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Protein/Low-Carbohydrate Diet versus a Standard Hypocaloric Diet on Weight and Cardiovascular Risk Factors: Role of a Genetic Variation in the rs9939609 <b><i>FTO</i></b> Gene Variant

Abstract: Background and Aims: The common polymorphism rs9939609 of the fat mass- and obesity-associated gene (FTO) has been linked to obesity. Our aim was to investigate its role in weight loss after the administration of a high-protein/low-carbohydrate diet compared to a standard hypocaloric diet (1,000 kcal/day). Methods: During 9 months, 195 patients were randomly allocated to a high-protein hypocaloric diet (HP diet) and a standard hypocaloric diet (S diet). Results: With the HP diet, BMI (-1.9 ± 1.2 vs. -2.10 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…These results suggest that dietary protein can mitigate the genetic risk associated with FTO . These findings were replicated in a recent weight loss trial which found that those with the FTO risk allele had greater weight loss and greater improvement in various metabolic parameters when placed on a high-protein diet [ 31 ]. However, a study of over 16,000 children from 14 study populations found that the adverse effects of variation in FTO on BMI were attenuated by low, rather than high, protein intake [ 38 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These results suggest that dietary protein can mitigate the genetic risk associated with FTO . These findings were replicated in a recent weight loss trial which found that those with the FTO risk allele had greater weight loss and greater improvement in various metabolic parameters when placed on a high-protein diet [ 31 ]. However, a study of over 16,000 children from 14 study populations found that the adverse effects of variation in FTO on BMI were attenuated by low, rather than high, protein intake [ 38 ].…”
Section: Discussionmentioning
confidence: 82%
“…Those who carried at least one copy of the FTO rs1558902 risk allele (A) experienced significantly greater reductions in body mass and fat distribution in response to a high-protein diet compared to T allele homozygotes, while this effect of FTO genotype was not observed in the low-protein treatment group. This interaction between dietary protein and FTO genotype on weight loss has been replicated in a population of obese adults in Spain [ 31 ]. However, the majority of participants in these studies were Caucasian, and it is unclear whether the FTO variants interact with dietary protein intake to influence measures of body weight in individuals of diverse ethnocultural backgrounds.…”
Section: Introductionmentioning
confidence: 86%
“…Numerous systematic reviews and meta-analyses support the role of the rs9939609 variant on alpha-ketoglutarate-dependent dioxygenase (FTO) in both dietary intake (20) and diet-related weight loss (21). This variant also appears to influence the response to macronutrient intake, although the evidence is mixed (22)(23)(24). More studies are needed and the effect sizes of the FTO associations are generally modest.…”
Section: Nutritional Genetics and Cancer: Personalized Nutrition In Cmentioning
confidence: 99%
“…In this study, the observed rates of obesity or overweight were similar in FTO variants while diet-disease relationships were found to be different. In this study, FTO risk alleles (AA) were observed to be more responsive to dietary changes than other variants (30). The reduction in food-craving response to a high-protein diet intake is also associated with the FTO A allele.…”
Section: Discussionmentioning
confidence: 82%